Implementation of Active Learning in Multi-site Pai Learning at Sma Negeri 1 and Smk Negeri I Kotacane, Southeast Aceh District - Saripah Aini; Siahaan, Amiruddin; Ira Suryani (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2024)
This study aims to analyze the Implementation of Active Learning in Islamic Religious Education Learning at SMA Negeri 1 and SMK Negeri 1 Kotacane, Southeast Aceh Regency. This research aims to reveal; 1) Planning of Active Learning Implementation in Islamic Religious Education Learning, 2) Implementation of Active Learning in Religious Education learning, 3) Evaluation of the Implementation of Active Learning in Islamic Religious Education learning at SMA Negeri 1 and SMK Negeri 1 Kotacane, Southeast Aceh Regency This research uses a type of qualitative research, with a critical discourse analysis approach, research data collection obtained by observation, interview and documentation techniques. To check the validity of the data using triangulation techniques, namely with credibilty, transferability, dependability and confirmability. The results of this study there are three findings of this study, namely: 1) Planning of Active Learning Implementation in Islamic Religious Education learning, 2) Implementation of Active Learning Implementation in Islamic Religious Education learning, 3) Evaluation of Active Learning Implementation in learning Islamic Religious Education at SMA Negeri 1 and SMK Negeri 1 Kotacane, Southeast Aceh Regency. The majority experienced a significant increase in two aspects, namely cognitive and psychomotor aspects.